2012
DOI: 10.1371/journal.pmed.1001155
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival in a Large Cohort of Patients with Venous Thrombosis: Incidence and Predictors

Abstract: Linda Flinterman and colleagues report on the long-term mortality rate for individuals who have experienced a first venous thrombosis or pulmonary embolism. They describe an ongoing elevated risk of death for individuals who had experienced a venous thrombosis or pulmonary embolism as compared to controls, for up to eight years after the event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
86
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 20 publications
9
86
2
5
Order By: Relevance
“…Each DOAC was compared with LMWH + VKA in the reference case, and the results are presented in a tornado plot. 7,24 1.00 NA DVT utility penalty 6,7 0.84 (0.63-1.00) Uniform PE utility penalty 6,7 0.76 (0.57-0.95) Uniform Major bleeding utility penalty 6,7 0.66 (0.50-0.83) Uniform Background mortality 26 2.0 (1.50-2.5)…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…Each DOAC was compared with LMWH + VKA in the reference case, and the results are presented in a tornado plot. 7,24 1.00 NA DVT utility penalty 6,7 0.84 (0.63-1.00) Uniform PE utility penalty 6,7 0.76 (0.57-0.95) Uniform Major bleeding utility penalty 6,7 0.66 (0.50-0.83) Uniform Background mortality 26 2.0 (1.50-2.5)…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] A recent study reported an 8-year mortality risk of 12%, 1 whereas in an earlier study, mortality risk reached 50% after 8 years of follow-up. 5 Previous studies were limited by short follow-up time (maximum, 10 years), [1][2][3][4][6][7][8][9][10][11] age restrictions (<70 years of age 1 or between 65 and 89 years of age 7 ), lack of adjustment for comorbidity 3,12 or calendar period, 3,5 and failure to examine mortality for DVT and PE separately. 1,8,12 Only a few studies have compared long-term mortality between VTE patients and a comparison cohort from the general population, with inconsistent results.…”
mentioning
confidence: 99%
“…person-years (95% CI 21.0 -24.6) for patients and 4.7 per 1000 person-years (95% CI 4.0 -5.6) for controls [19]. Also, Flinterman et al found that patients with VTE had a 4.0-fold (95% CI 3.7 -4.3) risk of death compared with the control group.…”
Section: Prognosismentioning
confidence: 98%
“…Flinterman et al examined the long-term survival rate in a large cohort of 8 years [19]. The study found that the overall mortality rate was 22.7 per 1000…”
Section: Prognosismentioning
confidence: 99%
See 1 more Smart Citation